Answer:
0=0
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
4(3y−6)=−3(8−4y)
(4)(3y)+(4)(−6)=(−3)(8)+(−3)(−4y)(Distribute)
12y+−24=−24+12y
12y−24=12y−24
Step 2: Subtract 12y from both sides.
12y−24−12y=12y−24−12y
−24=−24
Step 3: Add 24 to both sides.
−24+24=−24+24
0=0
Answer:
the picture is blurry
Step-by-step explanation:
Answer:
-13c-4
Step-by-step explanation:
Answer:
Reciprocal
Step-by-step explanation:
meaning the fraction flipped
Answer: no, you add the exponents.
Step-by-step explanation: